2015
DOI: 10.17221/817/2014-pse
|View full text |Cite
|
Sign up to set email alerts
|

Zinc fertilization alters flour protein composition of winter wheat genotypes varying in gluten content

Abstract: Wheat flour protein components affect the processing quality of wheat. While it is known that zinc (Zn) fertilization can change flour protein content, there is little knowledge about Zn influence on flour protein composition. A pot experiment was conducted with five Zn fertilization treatments and three wheat genotypes differing in protein concentration and gluten composition. Zn fertilization up to 10 mg Zn/kg soil increased activity of nitrate reductase and glutamine synthetase in flag leaves after flowerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 23 publications
1
7
0
2
Order By: Relevance
“…The addition of Zn fertilizer increased grain yield, total protein, albumin, gliadin, and glutenin content, but decreased globulin content. In agreement with H. E. Liu et al (2015) the largest effect on grain yield and protein composition was observed at an addition level of 15 mg Zn/kg soil. The negative effects of HTS on wheat quality were partially mitigated by Zn fertilization, but the underlying regulatory mechanisms still need to be clarified (Tao et al, 2018).…”
Section: Factors Affecting the Quantity Of Wheat Gluten Proteinssupporting
confidence: 90%
See 1 more Smart Citation
“…The addition of Zn fertilizer increased grain yield, total protein, albumin, gliadin, and glutenin content, but decreased globulin content. In agreement with H. E. Liu et al (2015) the largest effect on grain yield and protein composition was observed at an addition level of 15 mg Zn/kg soil. The negative effects of HTS on wheat quality were partially mitigated by Zn fertilization, but the underlying regulatory mechanisms still need to be clarified (Tao et al, 2018).…”
Section: Factors Affecting the Quantity Of Wheat Gluten Proteinssupporting
confidence: 90%
“…Next to the positive effect on human nutrition, Zn fertilization with 5–20 mg Zn/kg soil has been shown to increase grain and flour protein content of three Chinese wheat varieties by increasing albumins, globulins, gliadins, and glutenins. The results were variety‐dependent and indicated that 10–20 mg Zn/kg soil were the optimal dose, because a higher dose (40 mg Zn/kg soil) led to a subsequent decrease of all protein components (H. E. Liu et al, 2015). Tao et al (2018) investigated the effect of four levels of Zn fertilizer (0, 15, 30, and 45 mg Zn/kg soil) combined with normal temperature or high‐temperature stress (HTS, 38°C for 2 days) at 20 days postanthesis on wheat protein content and composition.…”
Section: Factors Affecting the Quantity Of Wheat Gluten Proteinsmentioning
confidence: 99%
“…It was hypothesized that the foliar fertilization of both ZnSO 4 and ZnO NPs would improve the grain yield and Zn concentration as well as improving grain quality. Starch and sugars have important effects on grain quality and are the major carbohydrate components in wheat grains, being mostly stored in the endosperm. , The grain protein content is also an important factor in determining quality . Normally, prolamin and glutelin components account for 66–87% of the total protein in wheat grain.…”
Section: Results and Discussionmentioning
confidence: 99%
“…14,39 The grain protein content is also an important factor in determining quality. 40 Normally, prolamin and glutelin components account for 66−87% of the total protein in wheat grain. Although the proportions of albumin and globulin are comparatively small, they are rich in lysine and have a higher nutritional value.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The reason might be due to the rapid absorption and transportation of foliar nano-Zn with the involvement of several factors (i.e., thickness, density, and chemical composition of cuticle, trichomes, and stomata conductance), which are responsible for the operation of the entire plant machinery and, thus, improving metabolic and biochemical processes of the plants ( Yumei et al., 2014 ; Xie et al., 2020 ). Zn fertilization increases grain reserve proteins because of its involvement in nitrate reductase activities and nitrogen assimilation pathways ( Liu et al., 2015 ; Silva et al., 2021 ). Zn fertilization has also reported that co-application of Zn and PGPBs could modulate plant defensive system by improving photosynthetic pigments and primary metabolites, leading to better plant performance and yield ( Tanveer et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%